Illicit Activity and Money Laundering from an Economic Growth Perspective : A Model and an Application to Colombia - Villa, Edgar (World Bank, Washington, DC, 2016)
This paper contributes to the economic analysis of illicit activities and money laundering. First, it presents a theoretical model of long-run growth that explicitly considers illicit workers, activities, and income, alongside a licit private sector and a functioning government. Second, it generates estimates of the size of illicit income and provides simulated and econometric estimates of the volume of laundered assets in the Colombian economy. In the model, the licit sector operates in a perfectly competitive environment and produces a licit good through a standard neoclassical production function. The illicit sector operates in an imperfectly competitive environment and is composed of two different activities: The first activity produces an illicit good that nonetheless is valuable in the market (for example illicit drugs); the second does not add value to the economy but only redistributes wealth (for example robbery, kidnapping, and fraud). The paper provides a series of comparative statics exercises to assess the effects of changes in government efficiency, licit sector productivity, and illicit drug prices. From the model, the analysis derives a set of estimable macroeconometric equations to measure the size of laundered assets in the Colombian economy in the period 1985 to 2013. The paper assembles a data set whose key components are estimates of illicit income from drug trafficking and common crime. Illicit incomes increased drastically until 2001, reaching a peak of nearly 12 percent of gross domestic product and then decreasing to less than 2 percent by 2013. The decline overlaps not only in a period of high economic growth, but also after the implementation of Plan Colombia. The data set is used to estimate the volume of laundered assets in the economy by applying the Kalman filter for the estimation of unobserved dynamic variables onto the derived macroeconometric equations from the model. The findings show that the volume of laundered assets increased from about 8 percent of gross domestic product in the mid-1980s to a peak of 14 percent by 2002, and declined to 8 percent in 2013.